2022
DOI: 10.1111/ene.15545
|View full text |Cite
|
Sign up to set email alerts
|

Subtle vascular and astrocytic changes in the brain of coronavirus disease 2019 (COVID‐19) patients

Abstract: Background and purpose In the central nervous system, a multitude of changes have been described associated with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, such as microglial activation, perivascular lymphocyte cuffing, hypoxic‐ischaemic changes, microthrombosis, infarcts or haemorrhages. It was sought here to assess the vascular basement membranes (vBMs) and surrounding perivascular astrocytes for any morphological changes in acute respiratory syndrome (coronavirus di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 61 publications
1
13
1
Order By: Relevance
“…In healthy astrocytes, subcellular AQP4 distribution is polarized and AQP4 is mainly located in the astrocyte endfeet surrounding blood vessels, where it functionally contributes to the blood-brain barrier and is involved in extracellular volume dynamics, water homeostasis and waste clearance (Nagelhus & Ottersen, 2013; Rasmussen, Mestre, & Nedergaard, 2022; Verkman, Smith, Phuan, Tradtrantip, & Anderson, 2017). We found increased AQP4 expression and loss of AQP4 polarization in all COVID-19 patients investigated, in contrast to a former study that showed decreased AQP4 (Rosu et al, 2022). Malfunction of AQP4 contributes to the progression of neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease, and AQP4 autoantibodies cause neuromyelitis optica spectrum disorder (Buccellato, D’Anca, Serpente, Arighi, & Galimberti, 2022; Mader & Brimberg, 2019; Nedergaard & Goldman, 2020; Pittock, Zekeridou, & Weinshenker, 2021).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In healthy astrocytes, subcellular AQP4 distribution is polarized and AQP4 is mainly located in the astrocyte endfeet surrounding blood vessels, where it functionally contributes to the blood-brain barrier and is involved in extracellular volume dynamics, water homeostasis and waste clearance (Nagelhus & Ottersen, 2013; Rasmussen, Mestre, & Nedergaard, 2022; Verkman, Smith, Phuan, Tradtrantip, & Anderson, 2017). We found increased AQP4 expression and loss of AQP4 polarization in all COVID-19 patients investigated, in contrast to a former study that showed decreased AQP4 (Rosu et al, 2022). Malfunction of AQP4 contributes to the progression of neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease, and AQP4 autoantibodies cause neuromyelitis optica spectrum disorder (Buccellato, D’Anca, Serpente, Arighi, & Galimberti, 2022; Mader & Brimberg, 2019; Nedergaard & Goldman, 2020; Pittock, Zekeridou, & Weinshenker, 2021).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, astrocytes are affected by and are often causal of neurological diseases (Lee, Wheeler, & Quintana, 2022; Lohr, 2023; Patel, Tewari, Chaunsali, & Sontheimer, 2019). In COVID-19, reactive astrogliosis has been reported, including increased expression of glial fibrillary acidic protein (GFAP), and glial markers were found elevated in plasma and cerebrospinal fluid (Hanson et al, 2022; Huang & Fishell, 2022; Kanberg et al, 2020; Rosu et al, 2022; Spanos et al, 2022; Steardo, Steardo, & Scuderi, 2022; Tremblay et al, 2020). In the present study, we investigated the astrocyte markers GFAP, calcium-binding protein S100B and aquaporin-4 (AQP4) as well as microgliosis in frontal lobe of COVID-19 brains using immunohistochemical staining and compared the results with those from control brains.…”
Section: Introductionmentioning
confidence: 99%
“…Perivascular cu ng (Fig. 4b) is well described in histological examinations of brains from deceased COVID-19 patients 42,43,66,101,102 . Other lesions observed in the BA.5-infected K18-hACE2 mouse brains, that have also been described in post-mortem COVID-19 patients, include perivascular edema (Fig.…”
Section: Lesions In the Brains Of Ba5 Infected K18-hace2 Mice Identi ...mentioning
confidence: 65%
“…Perivascular cuffing (Fig. 3b) is well described in histological examinations of brains from deceased COVID-19 patients 38,39,56,87,88 . Other lesions observed in the BA.5-infected K18-hACE2 mouse brains, that have also been described in post-mortem COVID-19 patients, include perivascular edema (Fig.…”
Section: Lesions In the Brains Of Ba5 Infected K18-hace2 Mice Identif...mentioning
confidence: 67%
“…4D) (Al-Dalahmah et al, 2020; Awogbindin et al, 2021; Matschke et al, 2020; Schwabenland et al, 2021), and occasional small hemorrhagic lesions (Fig. 4E) (Mukerji and Solomon, 2021; Rosu et al, 2022). XBB infected mouse brains showed very similar lesions (Fig.…”
Section: Resultsmentioning
confidence: 97%